Pengaruh Brand Ambassador Terhadap Motivasi Penggunaan Aplikasi Belajar Ruang Guru - Bintang Nurul Fikri; Novinda Salma; Vivi Fajri (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This research was conducted to find out and analyze the effectiveness of Brand Ambassadors on the motivation to use the teacher's room learning application. This research is a quantitative study using primary data obtained from questionnaires and measured using a Likert scale. Data were analyzed using a simple regression test. The population of this study was SMA N 1 Muntilan with a total of 1,065 students where the sample taken was only 10% or 90 students who were sampled for this study. The results of this study indicate that brand ambassadors have an influence on the motivation to use the teacher's room learning application.